ТОРГІВЛЯ КВОТАМИ НА ВИКИДИ ПАРНИКОВИХ ГАЗІВ: ОБЛІКОВИЙ ПІДХІД - Zamula, Iryna; Kireitseva, Anna; Travin, Vitaliy; Berlyak, Halyna; Paliy, Olga (Zhytomyr Ivan Franko State University, 2022)
Over the last century, there has been a significant increase in the concentration of greenhouse gases in the atmosphere. This calls for the study of global climate change and the search for mechanisms to influence such change. The purpose of the study is to outline the legal and economic prerequisites for trading in greenhouse gas emission allowances, the formation of its accounting support based on the definition of the nature of quotas and their classification. The United Nations Framework Convention on Climate Change, and later the Kyoto Protocol and the Paris Agreement, aim to use the world's economic mechanisms to prevent climate change. The Paris Climate Agreement stipulates that all states, regardless of their level of economic development, undertake to reduce harmful emissions into the atmosphere. The economic instruments of the state policy on decarbonisation include: the system of greenhouse gas emission allowance trading and the environmental tax on greenhouse gas emissions. In order to provide reliable information on the number of quotas for greenhouse gas emissions, which directly affects the amount of quotas to be implemented, they must be reflected in the accounting of enterprises. It has been proven that quotas for greenhouse gas emissions from the point of view of accounting are an intangible asset in the form of a permit for greenhouse gas emissions into the atmosphere. It is proposed to divide the quota for greenhouse gas emissions into target and surplus. At the same time, excess quotas by source of income are divided into government and other countries' quotas. The main significant shortcoming in the functioning of the greenhouse gas emission allowance trading system is the lack of an accounting system for greenhouse gas emission allowances, which makes it impossible to obtain reliable information on allowance trading transactions at the level of enterprises that are major players in the internal market. The issue of accounting for greenhouse gas emission allowances is a prospect for further research.